2023
DOI: 10.3390/molecules28062751
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Activation by Nitrogen Heterocycles: A Review

Abstract: Several nitrogen heterocyclic analogues have been applied to clinical practice, and about 75% of drugs approved by the FDA contain at least a heterocyclic moiety. Thus, nitrogen heterocycles are beneficial scaffolds that occupy a central position in the development of new drugs. The fact that certain nitrogen heterocyclic compounds significantly activate the NRF2/ARE signaling pathway and upregulate the expression of NRF2-dependent genes, especially HO-1 and NQO1, underscores the need to study the roles and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 159 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…This notion is supported by the fact that a large number of the USA Food and Drug Administration (FDA)-approved drugs contain one or several heterocyclic rings in their structures. 1–3 Therefore, access to a chemical library of small molecules containing one or more “privileged” heterocyclic rings is generally considered a prerequisite for effective drug discovery endeavors. 4,5 Among them, sulfur-containing heterocycles are gaining attention in organic synthesis due to their applications in materials sciences, pharmaceutical industries, and food chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by the fact that a large number of the USA Food and Drug Administration (FDA)-approved drugs contain one or several heterocyclic rings in their structures. 1–3 Therefore, access to a chemical library of small molecules containing one or more “privileged” heterocyclic rings is generally considered a prerequisite for effective drug discovery endeavors. 4,5 Among them, sulfur-containing heterocycles are gaining attention in organic synthesis due to their applications in materials sciences, pharmaceutical industries, and food chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, oxidative stress has been shown to play a significant role in the pathogenesis of several diseases through pro-oxidant factors altering several enzymes, cellular structures, gene expression, and mitochondrial physiology (Egbujor et al 2020b , 2023a ). Numerous studies have indicated that KEAP1 has an intracellular sensing ability to act as a homodimer on the cell’s redox status in modulating the biological functions of the transcription factor NRF2 (Suzuki and Yamamoto 2015 ; Egbujor et al 2023b ). (Cuadrado et al 2018 ) reported that NRF2 is a molecular target for protein–protein interaction within the cell for cytoprotective ability.…”
Section: Introductionmentioning
confidence: 99%
“…(Chen et al 2015 ) revealed that in the endothelial cell, NRF2–KEAP1 signaling plays a significant role in modulating the redox homeostasis, thus preventing several cardio-metabolic diseases like atherosclerosis, hypertension, aging, and ischemia, through combination with antioxidant response elements (ARE) and subsequently promoting several antioxidant genes transcription. During oxidative stress or inflammation, NRF2 dissociates from KEAP1, resulting in nuclear transcription processes (Egbujor et al 2023b ). (Yamamoto et al 2018 ) described the NRF2–KEAP1 system as a thiol-based biosensor regulating redox status in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…These heterocycles are widely recognized to be helpful for various applications, including drugs, therapeutic agents, fungicides, and agrochemicals, as well as for advanced materials [1] . The most common in biology and medicine are pyrrolidine, pyrroline, pyrazoles, quinoline, imidazoles, and pyrimidine derivatives [2] …”
Section: Introductionmentioning
confidence: 99%
“…[1] The most common in biology and medicine are pyrrolidine, pyrroline, pyrazoles, quinoline, imidazoles, and pyrimidine derivatives. [2] From the literature, we realized that organic compounds containing quinoline [3] cores, pyrazoles, [4] and pyrrole-fused Nheterocyclic structural units, [5] whether free or fused with other heterocycles is an active pharmacophore in many biologically important molecules including anti-inflammatory, antimalarial, antifungal, cardiac, antihelmintic, anticonvulsant, antibacterial, and pain-reducing properties. Some representative drugs having quinoline, pyrazoles, and pyrrolopyridines with biological and photophysical properties are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%